Inspired by National Museum / Muhammad Amzar Arman - Arman, Muhammad Amzar (2022)
The National Museum is one of the unique buildings in Malaysia. The National Museum is a museum located at Jalan Damansara, Kuala Lumpur, Malaysia. The museum is located near the Perdana Lake Garden. The National Museum has a combination of traditional Malay palace designs combined with modern tastes. The National Museum was officially opened on 31 August 1963.